1995
DOI: 10.1103/physrevlett.74.4067
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Determination of Chain-Structure Instability in KNbO3

Abstract: A complete mapping in the Brillouin zone of the structural instability associated with the ferroelectric phase transitions of KNbO 3 has been obtained by first-principles calculations using a linear response approach. The wavevector dependence of the instability reveals pronounced two-dimensional character, which corresponds to chains oriented along 100 directions of displaced Nb atoms. The results are discussed in relation to models of the ferroelectric phase transitions.Submitted to Phys. Rev. Lett.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
103
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 166 publications
(129 citation statements)
references
References 20 publications
25
103
0
Order By: Relevance
“…Further phonon analysis (17,18) on BaTiO 3 revealed two-dimensional character in the Brillouin zone, which corresponds to chains oriented along ͗100͘ directions of displaced Ti atoms. Such character had been found in KNbO 3 (19), a material with the same phase diagram as BaTiO 3 . In addition, the BaTiO 3 phonon analysis showed that X point instability is slightly less unstable than Gamma point in BaTiO 3 , implying a ferroelectric relaxation could lead to a lower-energy structure than an antiferroelectric relaxation.…”
mentioning
confidence: 96%
“…Further phonon analysis (17,18) on BaTiO 3 revealed two-dimensional character in the Brillouin zone, which corresponds to chains oriented along ͗100͘ directions of displaced Ti atoms. Such character had been found in KNbO 3 (19), a material with the same phase diagram as BaTiO 3 . In addition, the BaTiO 3 phonon analysis showed that X point instability is slightly less unstable than Gamma point in BaTiO 3 , implying a ferroelectric relaxation could lead to a lower-energy structure than an antiferroelectric relaxation.…”
mentioning
confidence: 96%
“…Overall, both B3LYP and GGA yield similar agreement with experiment, while RHF is significantly worse. Comparisons for the cubic and ferroelectric P4mm tetragonal BaTiO 3 phases should keep in mind evidence for static and/or motional disorder of local structures suggested by experiment 54,70,71 and theory, 72,73 since the present calculations were performed for ordered crystalline structures.…”
Section: Comparison Of Oxygen Chemical Shifts With Experimentsmentioning
confidence: 99%
“…The symmetry of the phonons determines the symmetry of the low temperature structure. This approach has been successfully used in the study of minerals [3,4,5] and ferroelectric materials [6,7,8,9] and has been extended to shape memory alloys in our previous study of NiTi [10].…”
Section: Introductionmentioning
confidence: 99%